Prediction of Sjögren's Syndrome Years Before Diagnosis and Identification of Patients With Early Onset and Severe Disease Course by Autoantibody Profiling. Issue 9 (September 2015) - Theander, Elke; Jonsson, Roland; Sjöström, Bitte; Brokstad, Karl; Olsson, Peter; Henriksson, Gunnel
<x xml:space="preserve">Abstract</x> Objective Autoantibodies are highly characteristic of primary Sjögren's syndrome (SS) and represent important tools for studying its pathogenesis. Nonetheless, thus far, no systematic investigations have assessed the presence of autoantibodies before diagnosis. This study was undertaken to analyze how early and in what order autoantibodies appear, how predictive they are of primary SS, and whether they identify disease subsets. Methods A nested case–control design linking data from the Malmö primary SS registry and 3 Swedish healthcare biobanks was applied. In all, 175 serum samples obtained from 117 individuals before diagnosis of primary SS and 1 serum sample from each of 117 matched controls were analyzed for antinuclear antibodies (ANAs), rheumatoid factor (RF), and antibodies against Ro 60/SSA, Ro 52/SSA, and La/SSB. Results Considering all patients with primary SS who were autoantibody positive after diagnosis, at least one autoantibody specificity was detected in 81% up to 20 years (median 4.3–5.1 years) before diagnosis. Those found most often were ANAs, followed by RF, anti–Ro 60/SSA, anti–Ro 52/SSA, and anti‐La/SSB. Anti‐Ro/SSA and anti‐La/SSB antibodies were strongly associated with the risk of developing primary SS, especially early‐onset disease and a severe disease course. When Bayesian prior prevalence estimates for primary SS were included in the calculation, prediagnostic anti–Ro 60/SSA and anti–Ro 52/SSA had the highest positive predictive values (25% and 100%, respectively). Conclusion Our findings indicate that autoantibodies are present for up to 18–20 years before the diagnosis of primary SS, but we cannot exclude even earlier seropositivity, since for most patients, the earliest sample analyzed was positive. In families with multiple cases of autoimmune disease, autoantibody profiling, along with assessment of genetic risk, enables identification of susceptible individuals in a predisease state.